2015
DOI: 10.1039/c5ta01632k
|View full text |Cite|
|
Sign up to set email alerts
|

High photocurrent in oligo-thienylenevinylene-based small molecule solar cells with 4.9% solar-to-electrical energy conversion

Abstract: A set of five novel oligo-thienylenevinylene organic molecules have been synthesized and characterized for use as electron donor moieties in bulk-heterojunction solution-processed organic solar cells combined with PC71BM as an electron acceptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…HornereWadswortheEmmons reaction of dialdehyde 5 [17] with the corresponding phosphonates 6 [18], 7 [19], and 8 [20] afforded central building blocks 9 [21], 10 [21], and 11 as trans-isomers according to NMR spectra ( 3 J trans ¼ 15.6 Hz). Subsequent VilsmeiereHaack formylation led to the corresponding dialdehydes 12 [21], 13 [21], and 14 after purification by chromatography column.…”
Section: Synthesis and Thermal Propertiesmentioning
confidence: 99%
“…HornereWadswortheEmmons reaction of dialdehyde 5 [17] with the corresponding phosphonates 6 [18], 7 [19], and 8 [20] afforded central building blocks 9 [21], 10 [21], and 11 as trans-isomers according to NMR spectra ( 3 J trans ¼ 15.6 Hz). Subsequent VilsmeiereHaack formylation led to the corresponding dialdehydes 12 [21], 13 [21], and 14 after purification by chromatography column.…”
Section: Synthesis and Thermal Propertiesmentioning
confidence: 99%
“…When comparing the literature on other A-D-A molecule solar cells, the device performance for SAM-72:PC 71 BM is competitive with that of other EDOT-based molecules. 44,47,48,74,75 For example, the material reported by Antwi et al (DECA-2TE), with equivalent side chains and a similar core, showed J sc values reaching an average of 2.99 mA cm À2 and FF of 39%. 47 Likewise, another group of EDOT-based materials reported in 2013 gave solar cell device performances with all FF values < 50%.…”
Section: Electrochemical Propertiesmentioning
confidence: 98%
“…44 Similarly, in the EDOT-based molecules reported by Montcada et al in 2013 (ref. 74) and 2015, 48 only two out of the six donor Fig. 4 Box plots for each optimization step for SAM-72:PC 71 BM devices:(a) donor to acceptor ratio, (b) thermal annealing temperature, and (c) thermal annealing + SVA time.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group presented a family of SMs smL02–06 (m116 – m120 ). Various π‐conjugated bridges and end‐capped group 3‐ethylrhodanine were introduced into smL01, and smL06 showed the highest PCE of 4.9% with an outstanding J SC of 12 mA cm −2 owing to the highest IPCE value . To determine the origin of high V OC s of these molecules, Tuladhar et al analyzed the V OC losses using electroluminescence and external quantum efficiency (EQE) measurements and the relationship between light absorption and emission.…”
Section: Structures Of A–π–d–π–a Electron‐donating Small Moleculesmentioning
confidence: 99%